Կենսագործունեության անբարենպաստ պայմաններում նախադպրոցականների վախերի դրսևորման առանձնահատկությունները (Տավուշի մարզի օրինակով) - Վիկտորյա Մելիքսեթյան (ՀՀ ԳԱԱ հրատ.)
There arе analyses of the children's tear characteristics, which were brought up in the terms of areal deprivation / ar example Tavush region/. Our research activities points that the fears among the children who lived in adwerse conditions were increased the age-specific norms.
Keywords: Psychology